Kinomics platform using GBM tissue identifies BTK as being associated with higher patient survival - Al Shboul, Sofian; Curran, Olimpia E; Alfaro, Javier A; Lickiss, Fiona; Nita, Erisa; Kowalski, Jacek; Naji, Faris; Nenutil, Rudolf; Ball, Kathryn L; Krejcir, Radovan; Vojtesek, Borivoj; Hupp, Ted R; et al. (Life science alliance, 2021)
Better understanding of GBM signalling networks in-vivo would help develop more physiologically relevant ex vivo models to support therapeutic discovery. A "functional proteomics" screen was undertaken to measure the specific activity of a set of protein kinases in a two-step cell-free biochemical assay to define dominant kinase activities to identify potentially novel drug targets that may have been overlooked in studies interrogating GBM-derived cell lines. A dominant kinase activity derived from the tumour tissue, but not patient-derived GBM stem-like cell lines, was Bruton tyrosine kinase (BTK). We demonstrate that BTK is expressed in more than one cell type within GBM tissue; SOX2-positive cells, CD163-positive cells, CD68-positive cells, and an unidentified cell population which is SOX2-negative CD163-negative and/or CD68-negative. The data provide a strategy to better mimic GBM tissue ex vivo by reconstituting more physiologically heterogeneous cell co-culture models including BTK-positive/negative cancer and immune cells. These data also have implications for the design and/or interpretation of emerging clinical trials using BTK inhibitors because BTK expression within GBM tissue was linked to longer patient survival.
Keywords: kokultivační techniky; Agammaglobulinaemia Tyrosine Kinase; Cell Line, Tumor; proteom; Proteome; nádorové buněčné linie; nádory mozku; lidé; proteinkinasa BTK; proteomika; signální transdukce; míra přežití; Signal Transduction; glioblastom; Glioblastoma; Proteomics; Neoplastic Stem Cells; Coculture Techniques; Brain Neoplasms; SOXB1 Transcription Factors; Survival Rate; Cell Survival; viabilita buněk; transkripční faktory SOXB1; nádorové kmenové buňky; Humans